Evaluation of Power Management Strategy for Renewable Microgrid System - Krishan Kumar; M. A. Ansari (IAES Indonesian Section, 2018)
This paper presents the evaluation and control of renewable energy sources based micro-grid system having solar photovoltaic, wind turbine generator, fuel cell and diesel engine generator. A battery storage system has also been installed to provide unintrupted power supply and to store excess power. The proposed micro-grid system is simulated on Matlab/Simulink software and the performance has been analysied with two cases considering different environmental conditions to check the optimal performance of the system. In the first case, the solar photovoltaic, fuel cell, diesel engine generator and battery storage system has been considered and in the second case, the solar photovoltaic source is replaced by the wind turbines. For both the cases, simulation has been done for 300 seconds to findout the optimal fulfilment of the demand. The time domain analysis has been done by varying the solar irradiance and wind speed in respective cases to check the system performance. This work shows the efficient control of various distributed energy resources in the micro-grid system and meeting the load demand efficiently.